The Effect of the GO-Expert Application on Ganesha Operation Student Satisfaction - Andy Yusuf Martua (Green Publisher Indonesia, 2025)
This study aims to analyze the impact of the GO-Expert application on student satisfaction at Ganesha Operation using the Technology Acceptance Model (TAM) approach. The research employed a quantitative descriptive method with a survey design and linear regression analysis. Data were collected through a closed questionnaire filled out by students using the e-learning system. The results indicate that the ease of use of the GO-Expert application positively influences perceived usefulness and attitudes toward its use. Although students recognize the benefits of the application, mandatory usage diminishes their interest in continuing to use the system. Overall, the findings suggest that behavioral attitudes positively affect behavioral intentions, which in turn influence the actual use of the GO-Expert application.